ANALISA DISPERSI PM2,5 MENGGUNAKAN MODEL GAUSS POINT SOURCE DIKAWASAN INDUSTRI DAN DESAIN VENTURI SCRUBBER BESERTA IPAL UNTUK EFFLUENT VENTURI (Studi Kasus : Industri Peleburan Aluminium PT.X Kecamatan Kesamben, Jombang) - Ida Dwi Maharani; Mohammad Razif (Program Studi Teknik Lingkungan, Universitas Pembangunan Nasional Veteran Jawa Timur, 2020)
The activity of aluminum smelting industry at X Ltd has decreased the quality of air around the industrial area as many people have complained about it. PM2,5 refers to one of particulates resulted from aluminum smelting process which gives negative effects to human health. This research aimed at analyzing the concentration of PM2,5 in the people’s settlement area by using gauss point source model as well as designing an air pollution controller of venturi scrubber for the kitchen of aluminum smelting and waste water treatment installation. The results of calculation demonstrated that the PM2,5 concentration at the industrial area of X Ltd point 1 (50 m from the industrial location) was 2.7 x 10-5 /m3, point 2 (100 m from the industrial location) as 6.7 x 10-6 /m3, point 3 (200 m from the industrial location) was 1.6 x 10-6 /m3. All the three points have fulfilled the quality standard of ambient air based on The Government Regulation of Indonesian Republic No. 41 Year 1999. The results of calculating the design of venturi scrubber indicated the dimension of throat diameter venture 0.55m, throat length 1.65 m, and diverging length 2.2 m. Moreover, the particulate removal of PM2,5 got 95%, whereas the design of Waste Water Treatment Installation presents the coagulation building having the dimension of length 0.86 m, width 0.86 m, and height 1.2 m, flocculation building with 2.1 m in length, l4.2 m in width, and 2 m in height, sedimentation building with 5.6 m in diameter and 1,57 m in height. Accordingly, the Cost budget Plan for designing Venturi Scrubber and Waste Water Treatment Installation is IDR. 83,647,421.